Haemoplasmosis in A Hypoalbuminemic Cat: A Case Report - Jayanti, Putu Devi; Gunawan, I Wayan Nico Fajar; Indarjulianto, Soedarmanto (Jurnal Medik Veteriner, 2023)
Haemoplasmosis is a bacterial infection in erythrocytes caused by Mycoplasma sp. This study aimed to report methods of diagnosis, therapy, and evaluation of therapy in cats with haemoplasmosis. The cat showed decreased appetite, conjunctivitis, presence of mucoid mucus on the eyes and nose, gum anemia with a capillary refill time of more than 2 seconds, high temperature, and weakness. Skin and hair examination reported infestations of Ctenocephalides felis and Lynxacarus sp. on the hair. Routine hematologic examination showed normochromic normocytic anemia, leukocytosis, neutrophilia, eosinophilia, lymphocytosis, monocytosis, and hypoalbuminemia. A blood test examination observed Mycoplasma sp. in erythrocyte cells so the cat was diagnosed with haemoplasmosis. Treatment was performed using Oxytetracycline long-acting at 20 mg/kg BW intramuscularly for 2 weeks and revealed support to recovery during the treatment period.